Overexpression, crystallization and preliminary X‐ray crystallographic analysis of hypothetical protein SAV0479 from Staphylococcus aureus Mu50. Issue 4 (2nd April 2013) - Pathak, Chinar; Jang, Sun‐Bok; Im, Hookang; Yoon, Hye‐Jin; Lee, Bong‐Jin
<x xml:space="preserve">Abstract</x> SAV0479, a hypothetical protein from the Mu50 strain of methicillin‐ and vancomycin‐resistant Staphylococcus aureus, was selected for structure and function determination as part of a structural genomics project. Here, the cloning, overexpression, purification and crystallization of SAV0479 are reported. Crystals were obtained by the hanging‐drop vapour‐diffusion method and diffraction data were collected to a resolution of 2.8 Å. The crystals belonged to space group P3121, with unit‐cell parameters a = b = 81.48, c = 82.53 Å. Three monomers of SAV0479 are present in each asymmetric unit.